INTEGRATED CURRICULUM MANAGEMENT MA'HAD TAHFIZ AL-QUR'AN AL-AMIEN PRENDUAN, SUMENEP - Hamzah, Moh (Sekolah Tinggi Ilmu Tarbiyah (STIT) Al-Ishlah Bondowoso, 2024)
This study aims to describe integrated curriculum management in Ma’had Tahfiz al-Qur'an Al-Amien Prenduan, Sumenep, Indonesia, including integrated curriculum planning, integrated curriculum implementation, and integrated curriculum evaluation. This study uses a qualitative approach with case study. The data collection is conducted with participatory observation, interview, and documentation. Data analysis uses data reduction techniques, data presentation, and conclusion. The results of the research in Ma'had Tahfiz al-Qur’an Al-Amien Prenduan are: 1) integrated curriculum planning are applied by integrating the objectives of the pesantren curriculum, tahfiz al-Qur’an curriculum, and school curriculum, as well as integrating the curriculum content organizing by grouping common subject, dirasat islamiyah, and tahfiz Qur'an. 2) Implementation of an integrated curriculum are done by unifying the education calendar and academic activity plans, both pesantren, tahfiz, and schools, as well as the integration of supervision. 3) Integrated curriculum evaluation which include: a) evaluation of curriculum context, b) evaluation of curriculum input, c) evaluation of curriculum process and d) evaluation of the curriculum products.